THE IMPACT OF RE-ENGINEERING HUMAN RESOURCES ON ADMINISTRATIVE CREATIVITY A FIELD STUDY IN THE GENERAL COMPANY FOR TEXTILE AND LEATHER INDUSTRIES (World Bulletin of Management and Law, 2023)
The research aims to identify the impact of re-engineering human resources on the administrative creativity of the General Company for Textile and Leather Industries and by increasing the level of clarity in the concepts and dimensions of the main and sub-variables by collecting and analyzing the opinions of researchers. The research problem crystallizes in a number of questions, the most important of which are the following: How to achieve the research sample Its goal is to continue and survive when applying human resources re-engineering and its impact on the process of administrative creativity. Where (120) questionnaires were distributed, which represents the sample size, while only (102) forms were subjected to analysis. The most important results were reached, namely: The statistical results extracted showed that the independent variable represented by (re-engineering human resources) had an effect of 89% on the dependent variable represented by (administrative creativity). The most prominent recommendations were: reducing gaps and weaknesses in senior management through Increasing participation in planning with all administrative levels to apply human resource re-engineering and explaining its importance as it constitutes its most important resource and the main driver for all its operations.